Knowledge about HIV/AIDS among the dental students in Dhaka - Jahan, Mohammed Shahed; Shaikh, Mushfiq Hassan; Begum, Jahanara; Chowdhury, Tazdik G; Hasan, Morshed (Update Dental College Journal, 2013)
Aims:This was a cross-sectional study done in the City Dental College, Malibagh, Chowdhurypara. The objective of the study was to assess the level of knowledge about HIV/AIDS among the final year dental students during the period between April to June 2012. Materials and Method:Convenient sampling technique was used and a total of 77 final year dental students were included. A pretested questionnaire was used in English and information was gathered by face to face interview regarding demographic characteristics and HIV/AIDS related knowledge which contained; meaning of HIV/AIDS cause of HIV/AIDS, mode of transmission, risk group, preventive measure. Result:The data were analyzed by computer software SPSS version 17. The study showed that 23.4 percent of the respondents had poor knowledge on HIV/AIDS. About 18.1% know that AIDS can be transmitted if having sexual contact with HIV positive case. Moreover, 13.8% have knowledge about HIV contaminated blood transfusion, 15.1% have knowledge about HIV infected mother to child, 14.6 % know that HIV infection can cause by pricking an infected needle and 10.5% know that it can transmit through body fluids like blood; semen etc. 45.1% had knowledge about injury by infected surgical instrument. Conclusion:The study revealed that the relationship between the knowledge of HIV/AIDS among dental students and sex of the respondents is statistically significant. It is evident that even in the second decade of the AIDS epidemic, final year dental students continue to have a lack of proper knowledge about HIV/AIDS. Training Programme should be arranged on HIV/AIDS for the dental students during clinical attachment. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15531 Update Dent. Coll. j: 2012; 2 (2): 23-27